Stratigraphy and petroleum geology of the Alexander silstone in Doddridge and Ritchie Counties, West Virginia - Cummings, Katie L. (East Carolina University, 2014)
The Upper Devonian Alexander siltstone is an informally named drillers' unit that occurs throughout the eastern half of the gas-producing portion of the Appalachian basin. The Alexander is primarily a gas-producing unit that extends from western New York and Pennsylvania south through West Virginia. In Doddridge and Ritchie counties in northwestern West Virginia the Alexander occurs within the Angola Member of the West Falls Formation and lies stratigraphically below the more prolific Benson sand reservoir. The purpose of this study is to determine the stratigraphic architecture of the Alexander in Doddridge and Ritchie counties to acquire a better understanding of the petroleum geology of the unit in the study area.   The gamma-ray signatures of the Alexander indicate three distinct siltstone intervals composed of intercalated siltstone bundles and thin shale layers that are separated from one another by intervals of shale that lack siltstone bundles. The Alexander intervals are referred to as the lower, middle, and upper Alexander in this study. The lower Alexander is the thickest interval and is laterally extensive across the study area. The gamma-ray signatures indicate that each Alexander interval has a sharp base with the abrupt appearance of siltstone bundles and a sharp or gradational upper boundary with the siltstone bundles fining-upward into shale. The siltstone bundles in the lower Alexander are coarsening-upward near the base and transition into fining-upward bundles near the upper boundary. The lower, middle, and upper Alexander are interpreted to represent distal depositional lobes within the fine-grained Upper Devonian turbidite system. The depositional lobes are thickest in the southern/southeastern portion of the study area and thin basinward to the west/northwest away from the sediment source. The individual siltstone bundles composing the Alexander are interpreted to be stacked siltstone turbidite deposits. The thin, discontinuous shale layers that are interbedded with the siltstone bundles were deposited from suspension between subsequent turbidity flows.   The log porosity of the Alexander intervals ranges from zero to eighteen percent within the study area, with the majority of the measurements ranging from zero to fourteen percent. The highest log porosities occur within the lower Alexander in laterally extensive porous zones and coincide with areas where the lower Alexander strata are thickest, suggesting that porosity is primarily related to the thickness of the interval. Available pay zone data indicate that hydrocarbon production is primarily from the lower Alexander and that production is primarily related to porosity in the study area.
Stratigraphy and petroleum geology of the Alexander siltstone in Doddridge and Ritchie Counties, West Virginia
Keywords: Geology; Petroleum geology; Alexander siltstone; Appalachian Basin; Stratigraphy; Upper Devonian; Geology, Stratigraphic; Petroleum--Geology--West Virginia--Doddridge County; Petroleum--Geology--West Virginia--Ritchie County; Siltstone--West Virginia--Doddridge County; Siltstone--West Virginia--Ritchie County